Impurity-Dependent Nanoporous Structures of Anodic Aluminum Oxides - Kyu Song, Chul; Kim, Dha-Hae; Jang, Se-Na; Yoo, So-Yeon; Hun Huh, Seung (Asian Journal of Chemistry, 2014)
With one-step anodizing, the highly nanoporous structures of anodic aluminum oxide were produced. The nanoporous structures were selectively formed in the combinatorial anodizing: (1) the low-purity aluminum and (2) phosphoric acid. The anodic aluminum oxide has unique structure with sprout-like surface, the main nanopores (180-210 nm) and the sub-nanopores at the bottom of main nanopores. This structure is explained by impurity model.